Business performance of MSMES in terms of entrepreneurial competencies and entrepreneurial orientation - Rahmi, Palupi Permata; Suryana, Suryana; Hendrayati, Heny; Aryanti, Asti Nur; Herlina, Listri (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2023)
This study aims to analyse the effect of entrepreneurial competencies and entrepreneurial orientation on business performance in the MSMEs Sub-Sector of Creative Industry in Bandung City. By distributing questionnaires to all respondents, the data sample is collected from 50 MSMEs. Quantities research method with SPSS analytical tool was used in this study. The results of this study indicate that entrepreneurial competencies partially affect business performance. Meanwhile, the entrepreneurial orientation variable partially influences business performance. Simultaneously, entrepreneurial competencies and entrepreneurial orientation affect business performance. The results of this research can be expected to contribute to the study of strategies and policies for the development of competencies and entrepreneurial orientation of MSMEs